RAD51 135G>C Single Nucleotide Polymorphism and Risk of Breast Cancer in Selected Filipino Cases. - Ragudo, G.
The RAD51 gene encodes the protein that plays a central role in the repair of DNA double-strand breaks (DSBs) through the homologous recombination pathway. Association of RAD51 single nucleotide genetic polymorphism (SNP) with the development of cancer has been observed to be tumor site- and race-specific. Thus, this study aimed to determine the potential association between RAD51 135G>C SNP and breast cancer among selected Filipinos. Patients with histologically confirmed breast cancer (n = 60) seen at the University of Santo Tomas Hospital (USTH Manila) were age- and sex-matched with clinically healthy controls (n = 60). Genomic DNA was extracted from the blood of participants and analyzed for RAD51 genotype by polymerase chain reaction ? restriction enzyme fragment length polymorphism (PCR-RFLP). A significantly higher incidence of RAD51 C/C genotype was seen among the cases than the controls (p < 0.05). The more common G/C genotype was not associated with breast cancer development, while the recessive less common C/C genotype was observed to potentially increase the risk. However, passive smokers carrying the RAD51 G/C genotype had a significantly increased chance of developing breast cancer. RAD51 G/C genotype ? even when combined with other established risk factors like alcohol use, active smoking, and family history ? were not associated with breast cancer.